An Overview on Citrus aurantium L.: Its Functions as Food Ingredient and Therapeutic Agent. (2nd May 2018) - Suntar, Ipek; Khan, Haroon; Patel, Seema; Celano, Rita; Rastrelli, Luca
Abstract : Citrus aurantium L. (Rutaceae), commonly known as bitter orange, possesses multiple therapeutic potentials. These biological credentials include anticancer, antianxiety, antiobesity, antibacterial, antioxidant, pesticidal, and antidiabetic activities. The essential oil of C. aurantium was reported to display marked pharmacological effects and great variation in chemical composition depending on growing locations but mostly contained limonene, linalool, and β -myrcene. Phytochemically, C. aurantium is rich in p -synephrine, an alkaloid, and many health-giving secondary metabolites such as flavonoids. Animal studies have demonstrated a low affinity of p -synephrine for adrenergic receptors and an even lower affinity in human models. The present review focuses on the different biological activities of the C. aurantium in animal and human models in the form of extract and its pure secondary metabolites. Finally, it is concluded that both the extract and isolated compounds have no unwanted effects in human at therapeutic doses and, therefore, can confidently be used in various dietary formulations.